Flexible bifunctional monoethylphosphonate/carboxylates of Zn(ii) and Co(ii) reinforced with DABCO co-ligand: paradigmatic structural organization with pcu topology. Issue 17 (14th April 2020) - Goldman, Anna; Gil-Hernández, Beatriz; Millan, Simon; Gökpinar, Serkan; Heering, Christian; Boldog, Ishtvan; Janiak, Christoph
Abstract : The prototypal [M2 (EtBCP)2 (DABCO)0.5 ] MOFs, compliant with isoreticular expansion in two-dimensions, show flexibility manifested by a two-step CO2 adsorption isotherm, which might be associated to the "lever-action" of the metal-phosphonate moieties. Abstract : Two novel isostructural phosphonate-monoethylcarboxylate MOFs with the structural formula of [M2 (EtBCP)2 (DABCO)0.5 ]·2DMA (M = Zn (2 ), Co (3 ); H2 EtBCP = O -ethyl- P -(4-carboxyphenyl)phosphonic acid, DABCO = 1, 4-diazabicyclo[2.2.2]octane, DMA = N, N -dimethylacetamide) were synthesized and characterized. The frameworks of 2 and 3 are sustained by Zn2 (PO2 (OEt))2 n metal-phosphonate- and DABCO-extended Zn2 (COO)4 (DABCO) n paddle-wheel carboxylate chain-SBUs. The chains providing connectivity in three, mutually orthogonal directions are running parallel and are combined in a framework, which could be interpreted as having a pcu topology. The simple structure-organization principle, which suggests the possibility of the elongation of the bifunctional ligand with scaling in two directions, allows to view the structures of 2 and 3 as prototypes for an isoreticular series. The porosity of both compounds, based on a relatively short ligand, is low: no adsorption of N2 was registered, however, CO2 is adsorbed readily allowing to estimate the surface area at ∼330 m 2 g −1 (∼900–1060 m 2 g −1 geometric estimate). The compounds demonstrate a two-step CO2 adsorption isotherm both at 195 K (0–1 bar) and 298 K (0–20 bar). The adsorption isotherms are characterized by a gradual (type "F-I"), albeit still relatively steep onset of the second step, associated with structural flexibility/bistability. The estimated pore volumes at the start of the transformation (195 K) for 2 and 3 are ∼0.11 (0.08 P / P 0 ) and 0.12 cm 3 g −1 (0.12 P / P 0 ) respectively, which corresponds considerably well to the geometrically calculated accessible volume of ∼0.07 cm 3 g −1 for the experimental structure (3.3 Å probe diameter). The structural prerequisites of the observed flexibility of the framework, which might be associated with the non-planarity of the metal-phosphonate moieties, acting as 'levers' for propagating mechanical stress, are discussed.